2009
DOI: 10.1111/j.1365-294x.2009.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape discontinuities influence gene flow and genetic structure in a large, vagile Australian mammal,Macropus fuliginosus

Abstract: Large vagile mammals typically exhibit little genetic structuring across their range, particularly when their habitat is essentially continuous. We investigated the population genetic structure of a large vagile Australian macropodid, Macropus fuliginosus, which is continuously distributed across most of southern Australia, using nine highly polymorphic nuclear microsatellite loci. Five distinct genetic units were identified across the range, four on the mainland and one on Kangaroo Island. In addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 113 publications
(143 reference statements)
3
44
0
Order By: Relevance
“…Even though, Pleistocene climatic changes affect patterns of intraspecific diversity [80], recent approaches have demonstrated that other causes, such as behavioural and morphological adaptations, may also influence dispersal and differentiation [81], [82]. Competition among males for local resources or mating chances (intrasexual selection) envisages a male-biased dispersal in polygynous species.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, Pleistocene climatic changes affect patterns of intraspecific diversity [80], recent approaches have demonstrated that other causes, such as behavioural and morphological adaptations, may also influence dispersal and differentiation [81], [82]. Competition among males for local resources or mating chances (intrasexual selection) envisages a male-biased dispersal in polygynous species.…”
Section: Discussionmentioning
confidence: 99%
“…These high levels of diversity may be a consequence of Kangaroo Island’s large size (Table 1), which has enabled the tammar wallabies to retain a large Ne since isolation from the mainland population and so reduce the impact of genetic drift [94,97]. Some macropodid populations on other large Australian islands, for example King and Flinders Islands, also show high diversity [98,99], although not the sympatric western grey kangaroo population on Kangaroo Island [78,100]. The now extinct SA mainland tammar wallaby population is therefore likely to have also been highly diverse, maybe even more so than surviving mainland populations in WA.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced diversity in WA populations is hypothesised from biogeography, since tammar wallabies are thought to have spread from eastern to western Australia across the arid Nullabor Barrier [77]. Similarly, in the western grey kangaroo, an expansion across southern Australia (although in the opposite direction) resulted in reduced genetic diversity in the more recently colonised population [78,95,100]. However, determining the original levels of diversity in SA and WA mainland tammar wallaby populations prior to their recent decline, and in SA extinction, is now almost impossible due to poor historic sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, postsettlement land clearing has proven beneficial to Western Grey Kangaroo ( Macropus fuliginosus ), causing range expansion and increased population density (Neaves et al . ). What then should we conserve: the pre‐European extirpated species, the invasive native species or some other species that performs a vital ecological function?…”
Section: Biogeography and Ecological Managementmentioning
confidence: 97%